MEDIA PEMBELAJARAN MATEMATIKA KOMIK PELUANG (KOLANG) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII SMP - Suci, Suci Indah Sari; Rusnita Dewi, Hefi; Zainuddin, Zainuddin (Jurnal Muara Pendidikan, 2024)
This research aims to develop an opportunity for comic mathematics learning media (KOLANG) to improve the critical thinking abilities of class VII junior high school students. The method used in this research is the Research and Development (R&D) method using the ADDIE development model. The data collection technique used is a validation sheet, while the data analysis technique used in this research is primary data. The research results show that the opportunity comic learning media (KOLANG) meets the feasibility standards in the very feasible category, with the results of the media expert validation assessment being 100% and the material expert validation assessment being 95%. So that the opportunity comic learning media (KOLANG) can be applied to support the learning process.